Determinants of the Adoption of Computerized Accounting Information Systems and the Perceived Effect on Financial Performance – A Case of Palestinian Companies - Ayman H. M. Uzrail; Bardai, Barjoyai (IJRDO - Journal of Business Management, 2019)
The Research aimed at investigating the adoption of computerized accounting information systems and its effect on the financial performance of companies (by increasing revenues and rationalizing expenses). To achieve the research objectives, the researcher designed a questionnaire based on the objectives and hypotheses of the study. The study population included all listed companies in Palestine. A total of 500 questionnaires was distributed to the CEOs of the companies and 495 were collected back and they were coded for the purposes of the analysis. The researcher used Analysis of Moment Structures (AMOS) and SPSS for data analysis and hypotheses testing. The findings of the study revealed that there is a significant relationship between the adoption of computerized accounting information systems (CAIS) and the perceived financial performance (PFP). Three independent variables - namely reliability of CAIS (RLB), efficiency of CAIS (EFC) and staff training (SFT) were also found to have significant impact on the perceived financial performance of the companies. The research concluded that management teams of all public listed companies in Palestine want to adopt the computerized accounting information systems to improve their financial performance. This survey result hopefully will enlighten management of Palestinian companies about the need to develop computerized accounting information systems to grow their financial performance. Future studies should focus on different variables and come up with new model.